Metformin mediates induction of miR‐708 to inhibit self‐renewal and chemoresistance of breast cancer stem cells through targeting CD47. Issue 9 (5th July 2019) - Tan, Weige; Tang, Hailin; Jiang, Xinhua; Ye, Feng; Huang, Lili; Shi, Dingbo; Li, Laisheng; Huang, Xiaojia; Li, Li; Xie, Xiaoming; Xie, Xinhua
Abstract: Breast cancer stem cells (BCSCs) have been considered responsible for cancer progression, recurrence, metastasis and drug resistance. However, the mechanisms by which cells acquire self‐renewal and chemoresistance properties are remaining largely unclear. Herein, we evaluated the role of miR‐708 and metformin in BCSCs, and found that the expression of miR‐708 is significantly down‐regulated in BCSCs and tumour tissues, and correlates with chemotherapy response and prognosis. Moreover, miR‐708 markedly inhibits sphere formation, CD44 + /CD24 − ratio, and tumour initiation and increases chemosensitivity of BCSCs. Mechanistically, miR‐708 directly binds to cluster of differentiation 47 (CD47), and regulates tumour‐associated macrophage‐mediated phagocytosis. On the other hand, CD47 is essential for self‐renewal, tumour initiation and chemoresistance of BCSCs, and correlates with the prognosis of breast cancer patients. In addition, the anti‐type II diabetes drug metformin are found to be involved in the miR‐708/CD47 signalling pathway. Therefore, our study demonstrated that miR‐708 plays an important tumour suppressor role in BCSCs self‐renewal and chemoresistance, and the miR‐708/CD47 regulatory axis may represent a novel therapeutic mechanism of metformin in BCSCs.